2015
DOI: 10.1186/1471-2415-15-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of selective laser trabeculoplasty for normal tension glaucoma: 1 year results

Abstract: BackgroundNormal tension glaucoma (NTG) is commonly treated with anti-glaucoma medications. Recently, selective laser trabeculoplasty (SLT) has been demonstrated to lower the intraocular pressure (IOP) and medication use in NTG. The purpose of this study was to investigate the efficacy of a single session of SLT for NTG at 1 year.MethodsThis prospective cohort study recruited NTG patients taking anti-glaucoma medication. Potential subjects were excluded if they had had previous glaucoma surgery or laser and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 25 publications
(25 reference statements)
4
71
1
4
Order By: Relevance
“…14,15 The Collaborative Normal-Tension Glaucoma Study Group has demonstrated that a 30% IOP reduction may slow disease progression of NTG despite a non-pressure dependent, hypoperfusion element in the disease pathophysiology. 16 Lee et al 6,17 prospectively treated 46 patients with NTG who were currently prescribed topical anti-glaucoma medications. They received a 1-month washout of medication and a single session of SLT before medications were gradually resumed in a step-wise manner.…”
Section: Normal-tension Glaucomamentioning
confidence: 99%
“…14,15 The Collaborative Normal-Tension Glaucoma Study Group has demonstrated that a 30% IOP reduction may slow disease progression of NTG despite a non-pressure dependent, hypoperfusion element in the disease pathophysiology. 16 Lee et al 6,17 prospectively treated 46 patients with NTG who were currently prescribed topical anti-glaucoma medications. They received a 1-month washout of medication and a single session of SLT before medications were gradually resumed in a step-wise manner.…”
Section: Normal-tension Glaucomamentioning
confidence: 99%
“…DED is mostly age related,1 but can also be triggered by refractive3,4 or cataract surgery 5–7. In addition, preexisting DED significantly increases the risk of prolonged or severe post-op signs and symptoms of dry eye 8,9. Refractive and cataract surgery patients have high visual expectations, and increasingly sophisticated intraocular lens and corneal ablation designs heighten the importance of good ocular surface health.…”
Section: Introductionmentioning
confidence: 99%
“…McBrien and Norton [78] have shown that preventing natural collagen crosslinking alone does not alter the refractive development but doubles the axial elongation rate when used together with form deprivation in juvenile tree shrews. A recent study by Wang and Corpuz [79] has shown that artificial crosslinking using genipin slows myopia development in guinea pig. These two experimental observations support the notion that collagen crosslinks modulate the maximum scleral remodeling rate.…”
Section: Discussionmentioning
confidence: 99%